Synthesis and reactivity of group 4 metal benzyl complexes supported by carbazolide-based PNP pincer ligands - Plundrich, Gudrun; Wadepohl, Hubert; Gade, Lutz H. (Inorganic chemistry, 2016)
This study focuses on the viability of the carbazole-based Cbzdiphos PNP pincer ligand as a stabilizing element for group 4 metal complexes, and both the diphenylphosphino- and di-isopropylphosphino-substituted Cbzdiphos protioligands 1PhH and 1iPrH were used. Treatment of the lithiated protioligands with the corresponding chlorido precursor compounds of the metals (titanium, zirconium, and hafnium) afforded the trichlorido complexes [(CbzdiphosiPr)MCl3] 2iPrM and [(CbzdiphosPh)MCl3] 2PhM (M = Ti, Zr, Hf), which were converted to the corresponding iodido complexes [(CbzdiphosiPr)MI3] 3iPrM and [(CbzdiphosPh)MI3] 3PhM (M = Ti, Zr, Hf) by reaction with an excess of trimethylsilyl iodide. Reaction of 2iPrTi and 3PhTi with 1 equiv of dibenzyl magnesium tetrahydrofuran adduct led to the formation of the alkylidene complexes 4iPrTi and 5PhTi, respectively, while the zirconium and hafnium complexes 2iPrZr and 3PhZr/Hf formed the cyclometalated monoalkyl compounds [(CbzdiphosiPr-CH)ZrBnCl] 6iPrZr as well as [(CbzdiphosPh-CH)MBnX] 6PhHf (X = Cl) and 7PhZr/Hf (X = I) under analogous reaction conditions. On the other hand, stirring 2PhZr with 0.25 equiv of tetrabenzyl zirconium afforded [(CbzdiphosPh)ZrBnCl2] (8PhZr), which contained the PNP ligand intact, while its alkylation with benzyl potassium led to the formation of the cyclometalated monobenzyl complex [(CbzdiphosPh-CH)ZrBnCl] (6PhZr). The remaining coordination site occupied by the halogenido ligand in the cyclometalated monobenzyl complexes [(Cbzdiphos-CH)MBnX] 6iPrZr, 6PhZr/Hf, and 7PhZr/Hf was readily benzylated by treatment with benzyl potassium to afford the cyclometalated dibenzyl complexes [(Cbzdiphos-CH)MBn2] 9iPrZr and 9PhZr/Hf. Further reaction of 9PhZr with an excess of benzyl potassium led to the formation of the anionic tribenzyl zirconium ate complex [(Cbzdiphos-CH)MBn3]K (10PhZr). Upon heating a solution of 8PhZr in the presence of 1 mol equiv of trimethyl phosphine, one of the ligand methylene groups was deprotonated, yielding the cyclometalated complex [(CbzdiphosPh-CH)ZrCl2(PMe3)] 11PhZr. Finally, reaction of 7PhZr with methylene triphenylphosphorane produced the ortho-metalated product [(CbzdiphosPh-CH)Zr(o-C6H4PPh2CH2)I] (12PhZr), which is characterized by a slightly puckered five-membered Zr-C(48)-P(3)-C(49)-C(50) metallacycle.
Published: December 18, 2015
Gesehen am 21.07.2020